Training Simple Analysis For Lake Water Pollution For The Nagari Community Of Kampung Batu Dalam Solok District, West Sumatra - Yusni Atifah; Violita Violita; Afifatul Achyar; Irma Leilani Eka Putri (Fakultas MIPA Universitas Negeri Padang, 2021)
The Nagari community of Kampung Batu Dalam as a community that lives around Lake Talang is a community that will get a direct impact from the existence of Lake Talang as a tourist destination in Solok City. In order to prepare for the Tourism Village, Nagari Kampung Batu Dalam needs to be equipped with knowledge and skills that will be useful for the Nagari Kampung community. Therefore, it is necessary to provide assistance to the people of Nagari Kampung Batu Dalam to increase public knowledge regarding pollution of lake waters, the impact of pollution and how to simply detect the presence of pollution in the lake. This activity was carried out in September 2021, and was attended by 15 participants from 10 youths representing the Batu Dalam community and 5 students from SMAN Batu Dalam. The results of the activity evaluation showed an increase in the knowledge of the Batu community regarding the conservation of Talang Lake and an increase in community skills in detecting simply the presence of pollution in Talang Lake water. In conclusion, this activity has been effectively carried out and can help the Batu Dalam community as an initial preparation towards Batu Dalam village as a tourist village